Effects of thermal barrier coating on the performance and combustion characteristics of a diesel engine fueled with biodiesel produced from waste frying cottonseed oil and ultra-low sulfur diesel - SAYIN, CENK (TAYLOR & FRANCIS INC, 2016)
In this study, the top surfaces of piston and valves of a four-strokes and direct-injection diesel engine have been coatedwith no change in the compression ratiowith a 100 m of NiCrAl lining layer via plasma spray method and this layer has later been coated with main coating material with a mixture of 88% of ZrO2, 4% of MgO and 8% of Al2O3 (400 m). Then, after the engine-coating process, ultra-low sulfur diesel (ULSD) as base fuels and its blend with used frying cottonseed oil derived biodiesel in proportion of 20%, volumetrically, have been tested in the coated engine and data of combustion and performance characteristics on full load and at different speeds have been noted. The results, which were compared with those obtained by uncoated-engine operation, showed that thermal efficiency increased, and engine noise reduced. Cylinder gas pressure values obtained from the diesel engine which has been coated with thermal barriers have been found to be somewhat higher than those of the uncoated-engine. Also, maximum pressure values measured in both engines and under the same experimental conditions through the use of test fuel have been obtained after TDC. Moreover, heat release rate and heat release have occurred earlier in the coated-engine. NOx emissions were increased while CO and HC emissions were remained almost the same with a little bit decrease.
Keywords: Combustion; diesel engine; engine coating; LHR; waste frying oil biodiesel; BLENDS; EMISSIONS